Особливості лексичної сполучуваності просторових прислівників-антонімів з дієсловами - Гончарук, Світлана Вікторівна; Єфремова, Наталія Володимирівна; Honcharuk, S. V.; Yefremova, N. V. (Східноєвропейський національний університет імені Лесі Українки, 2014)
У статті досліджено лексичну сполучуваність просторових прислівників-антонімів here-there, forward-back, close-far з дієсловами на рівні тематичних груп та лексичних одиниць. Функціональне дослідження просторових прислівників-антонімів за допомогою статистичних методів визначає актуальність роботи. Визначено тематичні групи дієслів, що сполучаються з досліджуваними прислівниками, та порівняно цю сполучуваність за допомогою статистичних методів. Новизна дослідження полягає в порівняльному аналізі лексичної сполучуваності просторових прислівників-антонімів з дієсловами відповідно до частоти, обсягу та лексичного наповнення тематичних груп дієслів. The article is devoted to the investigation of combinability of spatial adverbs-antonyms with verbs. The functional research of combinability of spatial adverbs-antonyms here-there, forward-back, far-close with the help of statistical methods determines the actuality of the given investigation. The purpose of the article is to determine the peculiarities of combinability of spatial adverbs here-there, forward-back, far-close with verbs on the level of thematic groups. The authors try to solve such tasks: to determine to investigate the combinability of spatial adverbs with verbs and to compare it. The novelty of the work lies in the comparative analysis of the combinability of thematic groups of adverbs according to their frequency and volume. On the basis of the given research the authors confirm the fact that adverbs here-there, forward-back, far-close combine with the verbs of motion, reflecting the unity of the main matter categories: time, space and motion.
The peculiarities of combinability of spatial adverbs-antonyms with verbs
Keywords: лексична сполучуваність; combinability; тематична група; thematic group